2020
DOI: 10.1029/2019jd032246
|View full text |Cite
|
Sign up to set email alerts
|

Linking Marine Biological Activity to Aerosol Chemical Composition and Cloud‐Relevant Properties Over the North Atlantic Ocean

Abstract: The ways in which marine biological activity affects climate, by modifying aerosol properties, are not completely understood, causing high uncertainties in climate predictions. In this work, in situ measurements of aerosol chemical composition, particle number size distribution, cloud condensation nuclei (CCN), and ice‐nucleating particle (INP) number concentrations are combined with high‐resolution sea surface chlorophyll‐a concentration (CHL) and back‐trajectory data to elucidate the relationship between oce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 98 publications
1
16
0
Order By: Relevance
“…Following the spatiotemporal correlation analysis approach (Mansour, Decesari, Bellacicco, et al., 2020 ; Mansour, Decesari, Facchini, et al., 2020 ; O'Dowd et al., 2015 ; Rinaldi et al., 2013 ), we investigated the spatial distributions of the correlation coefficient between cloud properties observed at MHD and sea surface CHL at each grid point of the NEA domain, considering different time‐lags from 0 to 25 days. Among all the analyzed cloud metrics, only R eff and CDNC demonstrated a robust and significant spatial correlation with CHL, which began to gradually diminish after time‐lag of 15 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the spatiotemporal correlation analysis approach (Mansour, Decesari, Bellacicco, et al., 2020 ; Mansour, Decesari, Facchini, et al., 2020 ; O'Dowd et al., 2015 ; Rinaldi et al., 2013 ), we investigated the spatial distributions of the correlation coefficient between cloud properties observed at MHD and sea surface CHL at each grid point of the NEA domain, considering different time‐lags from 0 to 25 days. Among all the analyzed cloud metrics, only R eff and CDNC demonstrated a robust and significant spatial correlation with CHL, which began to gradually diminish after time‐lag of 15 days.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the relationship between marine cloud properties and oceanic biological activity (represented by CHL), we implemented the spatio‐temporal correlation analysis approach (Mansour, Decesari, Bellacicco, et al., 2020 ; Mansour, Decesari, Facchini, et al., 2020 ). The approach is based on evaluating, by standard least squares regression, the correlation coefficients between the GBRS cloud parameters (the average of each variable in the 2D cloud profile; vertically‐ cloud thickness and horizontally‐ measurement time), measured at MHD, and sea surface CHL, at each grid point of the NEA domain.…”
Section: Methodsmentioning
confidence: 99%
“…Observations during previous deployments of Sea Sweep showed that the organic functional group composition of both seawater and gPMA were similar in the Atlantic, Arctic, and Pacific during spring and summer (Frossard et al, 2014) and that no significant differences exist between submicron organic mass fractions for five separate cruises in the North Atlantic (Bates et al, 2020). In all, while there are coastal observations that have shown links between marine biological activity and atmospheric organic aerosol (O'Dowd et al, 2004;Sciare et al, 2009;Mansour et al, 2020), there are very few remote marine observations that show a difference in the organic composition of gPMA under different biological conditions (Facchini et al, 2008).…”
Section: Introductionmentioning
confidence: 92%
“…However, by analyzing other biological components combined with atmospheric dynamics, Rinaldi et al (2013) showed a systematic delay between time series of oceanic Chl a and OM concentrations in atmospheric marine aerosols. That research indicated that not only biomass, but the dynamics of biological processes in oceanic surface waters with their respective timescales should be considered when ascertaining the biogenic organic contribution to primary marine aerosols (Rinaldi et al, 2013;Mansour et al, 2020). Other studies speculated that the presence of OM in SSA is linked to the decay of phytoplankton blooms and cell lysis rather than to the initial periods of proliferation and growth (O'Dowd et al, 2015).…”
Section: Introductionmentioning
confidence: 99%